THE EFFECT OF MANAGEMENT CAPABILITY ON THE PERFORMANCE OF BATIK SMES: THE ROLE OF SUSTAINABLE INNOVATION MEDIATION AND BUSINESS STRATEGY - Hendra Syahputra, Raden Andi Sularso, Ika Barokah Suryaningsih, Arnis Budi Susanto (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to test, analyze and explain the effect of management capabilities on the performance of Batik SMEs mediated by sustainable innovation and business strategy in East Java, Indonesia. This research’s design is explanatory research. The population is 2151UKM, and the sampling is done by using the Proportional random sampling method, using the Slovin formula with a sample size of 164 Batik UKM owners. Data were analyzed using descriptive methods and Partial Least Square (PLS). The findings of this study are that management ability has a significant positive effect on low-cost strategy and differentiation strategy (novelty); management ability has a significant positive effect on the performance of Batik SMEs; continuous innovation has a significant positive effect on low-cost strategies and differentiation strategies; management ability has a significant effect on continuous innovation; Low-cost strategy and differentiation strategy each have a significant effect on the performance of Batik SMEs.